Historical Background on the Limitation of Liability in Saudi Arabia (المجلة الدولية للبحوث العلمية, 2024)
This qualitative study explores the evolution and implications of limiting contractual liability in Saudi Arabia, focusing on the interplay between Sharia principles, international conventions, and domestic legal reforms. Through a comprehensive analysis of primary and secondary sources, including the new Civil Transactions Law 2023 and relevant legal documents, the research aims to thoroughly understand the historical roots and contemporary dynamics shaping contractual practices in Saudi Arabia. The study uncovers the challenges and opportunities inherent in harmonizing Sharia principles with global legal norms within the Saudi legal framework. Examining the new legislation reveals notable changes in the treatment of liability in commercial contracts, signaling a shift towards modernization and alignment with international standards. Its findings highlight the complexities of balancing contractual autonomy with legal constraints in the Saudi context, emphasizing the need for ongoing dialogue and research to address emerging issues and enhance the clarity and enforceability of contractual agreements. The study underscores the importance of a collaborative approach that integrates legal, cultural, and international perspectives to strengthen the legal framework and foster a conducive environment for commercial transactions in Saudi Arabia. In doing so, it offers a nuanced analysis of the legal landscape, shedding light on stakeholders' challenges and opportunities in navigating contractual practices within the Kingdom of Saudi Arabia.